Principles of chemical engineering processes : material and energy balances - Ghasem, Nayef; Henda, Redhouane (Boca Raton : CRC Press/Taylor & Francis Group, 2015)
'Preface Purpose of the Book The objective of this book is to introduce chemical engineering students to the basic principles and calculation techniques used in the field and to acquaint them with the fundamentals of the application of material and energy balances in chemical engineering. The book is mainly intended for junior chemical engineers. It exposes them to problems in material and energy balances that arise in relation to problems involving chemical reactors. The focus is on single and multiphase systems related to material and energy balances. This material is introduced in a manner that there will be little lecture content. Most of the material presented covers work on problem solving skills. The material intrusion theory is explained briefly and simply to make this book more user-friendly. Many examples are included and solved in a simple and understandable format that explains the related theory. A few examples related to unsteady state material and energy balance are solved using MATLAB
Includes bibliographical references and index.
Keywords: Chemical engineering